Pelayanan Medis pada Santri Pondok Pesantren Minhaajurrosyidiin Dan Masyarakat Sekitar - Pramudya, Dani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to provide medical services and health education to students of the Minhaajurrosyidiin Islamic Boarding School and the surrounding community who have limited access to health services. This activity is motivated by the high need for basic health checks and the lack of health education in the Islamic boarding school environment. The services provided include general health checks (blood pressure, blood sugar, nutritional status), medical consultations, provision of free medicines, and health education on Clean and Healthy Living Behavior (PHBS), balanced nutrition, and prevention of infectious diseases. The approach methods used are promotive, preventive, and curative by involving medical personnel from various professions such as doctors, nurses, and pharmacists. The results of the activity showed enthusiasm and active participation from more than 150 participants, both from students and residents around the Islamic boarding school. Evaluation through questionnaires and observations showed a very high level of participant satisfaction, as well as an increase in basic knowledge about health after the counseling. This activity shows the importance of collaboration between educational institutions, health workers, and the community in creating equitable access to health. It is expected that this kind of activity can be continued periodically with a wider scope and a stronger referral system, and involving internal health cadres from among the students as an effort to sustain the program.